Induction of chronic prostatitis does not alter the innate contractile properties of the prostate or urethra in rats - Ozgu Aydogdu; Gwenaelle Black; Patrik Aronsson; Thomas Carlsson; Michael Winder (Scientific Reports)
Abstract The current study aimed to examine how smooth muscle contractile properties and expression of functional proteins in the urethra and prostate are affected in an animal model of chronic prostatitis/chronic pelvic pain syndrome (CPPS). Thirty-two male Sprague-Dawley rats received an intraprostatic injection with saline or zymosan, serving as control and a model for CPPS, respectively. Two weeks later, the urethra and dorsal prostate were excised and studied functionally in organ baths. Following this, protein expression and urethral inflammation was examined immunohistochemically. Neither prostate nor urethra showed any significant changes in contractility compared to the control group, despite a tendency for increased cholinergic contractile responses in the CPPS urethra. Induction of CPPS led to an increased expression of muscarinic M3 receptors in the urethra. In the prostate, there were no significant differences in protein expression. HE staining showed no signs of inflammation in the urethra in either group. Previous studies have shown that CPPS can alter bladder contractility. Currently, CPPS did not affect contractile responses in neither prostate nor urethra. These findings are consistent with the theory of prostate-to-bladder cross-organ sensitization. Future studies exploring this may be of great relevance in the development of new treatment options for CPPS.